Training Of Business Analysis Using SWOT Method in Homestay “Omahe Wong Di Ino” Bantul Yogyakarta - Rinawati Zailani; Choirun Nisaa; Galih Sumarah Erilantu (Universitas Muhammadiyah Manado, 2023)
In a simple sense, a homestay is a whole house that is rented out to visitors to rest and with facilities like at home. The COVID-19 pandemic has brought businesses down. After the pandemic, business owners are trying to get back up to continue their business. One of the businesses that continues to try to rise after the pandemic is the homestay business